Biogasoline Production from Palm Oil Via Catalytic Hydrocracking over Gamma-Alumina Catalyst - Wijanarko, Anondho; Mawardi, Dadi Ahmad; Nasikin, Mohammad (UI Scholars Hub, 2006)
Biogasoline Production from Palm Oil Via Catalytic Hydrocracking over Gamma-Alumina Catalyst. Bio gasoline conversion from palm oil is an alternative energy resources method which can be substituted fossil fuel base energy utilization. Previous research resulted that palm oil can be converted into hydrocarbon by catalytic cracking reaction with γ-alumina catalyst. In this research, catalytic cracking reaction of palm oil by γ-alumina catalyst is done in a stirrer batch reactor with the oil/catalyst weight ratio variation of 100:1, 75:1, and 50:1; at suhue variation of 260 to 340oC and reaction time variation of 1 to 2 hour. Post cracking reaction, bio gasoline yield could be obtained after 2 steps batch distillation. Physical property test result such as density and viscosity of this cracking reaction product and commercial gasoline tended a closed similarity. According to result of the cracking product’s density, viscosity and FTIR, it can conclude that optimum yield of the palm oil catalytic cracking reaction could be occurred when oil/catalyst weight ratio 100:1 at 340 oC in 1.5 hour and base on this bio gasoline’s FTIR, GC and GC-MS identification results, its hydrocarbons content was resembled to the commercial gasoline. This palm oil catalytic cracking reaction shown 11.8% (v/v) in yield and 28.0% (v/v) in conversion concern to feed palm oil base and produced a 61.0 octane number’s bio gasoline.